Histopathological Observations of Minimally Invasive Gingival Connective Tissue Grafts in Monkeys - Kato, Hiroshi; Yabuta, Hideshi; Sakagami, Ryuji; Odajima, Tomoomi; Hongo, Okito (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 2000)
The purpose of this study was to verify the effectiveness of the newly developed minimally invasive gingival connective tissue graft technique by clinical andhistopathological observations in monkeys. The surgical procedure can be briefly explained as follows. First, the tip of a 14-gauge aspirating needle is sharpened so that it can be used as a gingival extraction tool. The aspirating needle is inserted in to the palatal gingiva (donor site) of the subject. After inserting the needle to a depth of about 5 mm, a scalpel is used to section off and extract the gingival tissue. Atthe recipient site, a small incision is made with a scalpel, and an 18-gauge injection needle is inserted intothe submucosa to shape a tunnel-like transplantation site. The previously extracted gingival tissue is placed in the tunnel with a small forceps, and as soon as the gingival transplantation has been completed, the site is sutured. Operations have been conducted on two macaques by using the procedure described above. The extracted gingival tissues were transplanted to 8 upper and lower labial sites as experimental sites and 2 labial sites were not transplantatied as control sites. Clinical and histopathological observations were made, during the next 12 weeks and the following results were obtained: 1. The operation required only a short period of time and was easy to perform. Wound healing was uneventful with minimum bleeding. 2. The clinical observations showed that both the keratinized gingiva and the attached gingiva were increased after 12 weeks, compared to their presurgical status. 3. The histopathological observations showed that the transplanted tissues were surrounded by scattered collagenous fiber tissue after 1 to 2 weeks. After 12 weeks, however, the tissue enclosing the transplanted gingiva had formed connective tissue with tightly meshed fibers that had firmly attached to the periosteum of the alveolar bone. The transplanted gingiva had been transformed into attached gingiva, and the overlying epithelium was keratinized as well. Based on the clinical and histopathological observations, compared to conventional mucogingival surgery, such as subpedicle connective tissue graft procedure, the new surgical method was minimally invasive and effective in achieving attached and keratinized gingiva. A modification of the new technique that excludes the epithelial tissue is also discussed. J. Jpn. Soc. Periodontol., 42: 192-199, 2000.